Estudo de casos de erosões hídricas lineares e seu controle na cidade de São Carlos e comparativo com outras regiões - Vivaldini, Amanda Ramela Schalch (Universidade Federal de São Carlos, 2021)
The rapid and disordered Brazilian population growth was characterized by the incorrect use of natural resources and, as a consequence, generated impacts and degradations to the environment, mainly in the soil. The soil represents a basic resource that supports all the vegetation cover on the planet, essential for the survival of life on Earth, which also supports the entire built infrastructure. One form of manifestation of this degradation is the erosive processes that can cause, in addition to significant loss of fertile soils, compromising its limit of soil loss, several environmental, economic and social impacts. This project aims to study cases of linear water erosion and how these erosions generate losses and correction works.A survey of cases was made on the causes and consequences of water erosions and, then, an analysis of techniques for recovering these erosions was conducted. In addition, an in-depth study of cases was carried out in the city of Sao Carlos, where the geotechnical characteristics of the cases studied were analyzed, through geotechnical maps of the city. It was possible to conclude that in urban areas the lack of planning and infrastructure in the implementation of subdivisions leads to most cases of erosion and in rural areas the replacement of vegetation by pastures and monoculture plantations are responsible for the erosive processes. In addition, through the study carried out it was found that erosion prevention and control techniques are often poorly dimensioned, without maintenance and in many cases did not exist. Regarding the city of Sao Carlos, it was possible to notice that the fragility of the physical environment, due to the type of rocky substrate and unconsolidated materials, added to the anthropic intervention, triggered the appearance of erosions.
Case study of linear water erosions and their control in the city of São Carlos and comparison with other regions
Keywords: Solo; Erosão hídrica; Técnicas de recuperação; ENGENHARIAS::ENGENHARIA CIVIL::GEOTECNICA